Mali : Technical Assistance Report. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Technical Assistance Report on Mali discusses automatic pricing mechanism options and identifies issues that need to be addressed for the application of such a mechanism. Mali stands to benefit from moving from the current discretionary approach to fuel product pricing to a transparent and automatic price adjustment mechanism. Although smoothing can help to mitigate the adverse impact of price increases and volatile international fuel prices, additional supporting policies are warranted. In particular, an effective safety net is required to protect the poorest and most vulnerable groups from the adverse impacts of sizeable domestic fuel price increases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet